Inhibitory Effects Of Neem Extracts On Banana, Anthracnose postharvest pathogen Colletotrichum musae - Nor Hazlin Hassan (FASM, Universiti Malaysia Terengganu (UMT), 2010)
Plant extracts for the control of plant disease are emerging as alternatives to conventional fungicide as they are generally safe to humans and environmentally friendly. Extracts of neem (Azadiracha indica) leaves were screened in vitro and in vivo against the fungal banana pathogen, Colletotrichum musae. Neem extracts inhibited mycelial growth of C. musae. A. indica extract at 20% concentration completely inhibited the growth of C. musae. Thus, this fungistatic concentration of neem extract was tested in vivo at room temperature (28°C) against anthracnose disease on the banana (Musa sepientum cv. Berangan). Neem extract was found to be very effective in reducing the incidence of disease better than a standard treatment with the fungicide benomyl. Neem extract showed lowest values on physicalchemical parameters such as chroma, firmness and total soluble solid compared with banana treated by benomyl and control. However, these neem extract was suitable to be used as biofungicide on inhibition of C. musae that cause anthracnose in bananas.